Modelling and simulation of ternary pumped storage hydropower for power system studies. Issue 19 (13th September 2019) - Dong, Zerui; Tan, Jin; St‐Hilaire, Antoine; Muljadi, Eduard; Corbus, David; Nelms, Robert; Jacobson, Mark
Abstract : As the deployment of wind and solar energy increases in the USA, energy storage (ES) will play an important role in future electric power grids to help manage the variability from high penetration levels of renewable generation, ES can provide promising power/energy demand to coordinate with renewables generation, as a virtual power plant (VPP). There is an industry need for the capability in power system studies to model ternary pumped storage hydropower (T‐PSH), a pumped storage technology that offers increased system benefits. This study presents a comprehensive vendor‐neutral dynamic model of T‐PSH in GE's commercial software positive sequence load flow. A new governor model is developed with detailed gate valve modelling and a shared‐penstock function. Specifically, this model is designed to simulate the seamless transition among three operation modes: generation mode, pumping mode, and hydraulic short‐circuit mode. The developed T‐PSH model has been tested and validated on a 10‐bus test system. A comparison study of T‐PSH to conventional pumped storage hydropower has also been conducted on the Western interconnection system.